Peranan Berbagai Jenis Bioaktivator dan Bahan Pengaya dalam Meningkatkan Kandungan Hara Kompos C. Odorata - Jamilah, Jamilah (Jurnal Embrio, 2008)
The role of bioactivators and abundance substances in increase the nutrient content of carbon organic manure held during 1,5 months at Padang. The goal of study was to get some of bioactivator and abundance substance in effort to increase nutrient of manure in accelerate the composting. The substance of green manure taken from Kuranji, Guano was come from Sungai Lansek Sawahlunto-Sijunjung District. Another substances added in compost was fertilizer like Urea, SP36, KCl and lime CaO. The Bioactivator were Biokom, EM4, Trichoderma. The treatment design was in complet random in four treatments and four replications. The treatment namely; Gulma C. odorata + guano (Krono) (A); Gulma C. odorata + Guano + Biocom (Kronobio) (B); Gulma C. odorata + Guano + Trichoderma (Kronotricho) (C); Gulma C. odorata + Guano + EM4 (Kronoem) (D); Gulma C. odorata + soil (Krota) (E).The Analysis of nutrient composition were; C-organic, N-total, P-available, P-total, pH and C/N ratio. The result suggest that in general to give the guano as abundance substance too help in increase of compost as than the soil. The bioactivator Trichoderma could in increase nitrogen content and the same time to reduce C-organic composition as as a result C/N ratio low. In general without some of bioactivator applied on composting material could be P-available and Total P higher than bioactivator application. The result that guano is important to be abundance substances in composting. The compost proccess bioactivator application could not be attached, because get compost quality.